Persetujuan Keluarga sebagai Syarat dalam Pemberian Pembebasan Bersyarat kepada Narapidana - Gusti Ngurah Agung Tresna Wangsa; I Ketut Sukadana; I Made Budiyasa (Warmadewa Press, 2020)
One of the rights of convict is obtaining parole. To get his right as a convict in order to get parole requires the consent of the convict's family as a guarantor. The aims of the research are to know the arrangement of parole to the convicts and to know the role of the family as a guarantor in granting parole to convicts. The method of research is the type of normative legal research. Approach of problem is approach of conceptual approach and legislation. Source of primary and secondary legal materials. Collection of legal materials by reading or studying books of legislation and other literature and added with the results of interviews. The analysis of legal materials is done by analytical descriptive. Results and discussion is the regulation of parole shall be granted to a convict who has served a criminal offense of at least 2/3 (two-thirds) with the provisions of 2/3 (two-thirds) of the criminal period not less than 9 (nine) months. it is regulated in Government Regulation no. 99 of 2012, Regulation of the Minister of Justice and Human Rights, Regulation of the Minister of Justice and Human Rights Number M.01.PK.04-10 of 2007, Ministerial Regulation no. 21 of 2013 which contains conditional pretrial conditions and procedures for convicts. Approval of the family as a guarantor is one of the mandatory requirement in granting conditional exemption to the convict because the family will be responsible in guiding and supervising the convict if they have obtained the Conditional Paragraph, providing information about the circumstances of the convicts and the family is also obliged to assist the economic condition because in general the convicts the newly acquired parole has not had a job yet.